2018
DOI: 10.3889/oamjms.2018.224
|View full text |Cite
|
Sign up to set email alerts
|

The Role of CYP2A6 Genetic Polymorphism in Nicotine Dependence and Tobacco Consumption among Bataknese Male Smokers

Abstract: AIM:This research aimed to analyse the relationship between CYP2A6 gene polymorphism with nicotine dependence and its relation to the number of cigarette consumption among Bataknese smokers.METHOD:This study was a cross-sectional study involving 140 research subjects in Medan, Indonesia.RESULTS:Nicotine dependence rates were found to be significantly associated with the number of cigarette consumption expressed in the Brinkman Index.CONCLUSION:The *1A wild-type alleles have a greater risk of high-very high dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 6 publications
3
9
0
Order By: Relevance
“…The Brinkman index in this study found that 75.7% of subjects were heavy smokers, 20% were moderate smokers, and the other 4.3% were light smokers. A similar result was also found by Soeroso et al, [ 15 ], [ 16 ] in which 52.9% of their research participants were categorised as heavy smokers. Also, this study was to evaluated nicotine dependence based on the Fagerstrom Tolerance Questionnaire (mFTQ), and the results showed that 65% of Fagerstrom scores were very high.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The Brinkman index in this study found that 75.7% of subjects were heavy smokers, 20% were moderate smokers, and the other 4.3% were light smokers. A similar result was also found by Soeroso et al, [ 15 ], [ 16 ] in which 52.9% of their research participants were categorised as heavy smokers. Also, this study was to evaluated nicotine dependence based on the Fagerstrom Tolerance Questionnaire (mFTQ), and the results showed that 65% of Fagerstrom scores were very high.…”
Section: Discussionsupporting
confidence: 89%
“…Globally, cigarettes are one of the biggest death factors with a 1:10 ratio in adults and a mortality rate of about 5 million people per year [ 14 ]. Similarly, a study conducted by Soeroso in 2018 showed that 60% of lung cancer cases suffered by patients aged 55-64 years [ 15 ], [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lung cancer found in the case was the adenocarcinoma type. A study by Soeroso et al [ 11 , 12 ] showed that the cytologic/histopathologic type which was mostly found was adenocarcinoma with approximately 92.9% compared with squamous cell carcinoma with approximately 7.1%. A proper enforcement of the diagnosis will be able to provide fast treatment so that the patient's quality of life will be better.…”
Section: Discussionmentioning
confidence: 99%
“…This may translate into inter-individual differences in the concentration of nicotine in the body and to differences in the number of cigarettes consumed by smokers [ 17 ]. For example, CYP2A6 reduced activity gene variants are associated with reduced lung cancer risk in smokers [ 18 , 19 ] and nicotine dependence [ 20 , 21 ] in different populations. While this variants are associated to increased risk for tobacco-related cancers in humans [ 22 – 24 ], they also can affect smoking-frequency, nicotine clearance, and data interpretation of tobacco use [ 25 ].…”
Section: Introductionmentioning
confidence: 99%